Growth and Moulting of Mud crab (Scylla serrata) By Giving Different Amounts of Trash Fish Feed and Cutting the Entire Foot of the Road - B Sianturi, Benny; Pamukas, Niken Ayu; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Feed is one of the major operating in cultivation of mud crab (S. serrata).One aspect for attention in cultivation were feeds. This research aims to determine the optimal effect of the feed percentage on the growth of mud crab aquaculture(S. serrata).This research was conducted using Experimental Methods with completely randomized design (CRD), those is 4 treatments and 3 replications. Treatment A (3% feeds of the weight biomass), B (5% feeds of weight biomass), C (7% feeds of weight biomass feed, D (9% feeds of weight biomass).Animal testing used was mud crab (S. serrata) with an average initial weight of ±100 gr / individual.Animal testing used were 48 crabs and maintained in a plastic basket measuring (59 x 37 x 17 )cm3during 40 day. The results shows different feed percentages had a significant effect (P <0.05) on absolute weight growth, feed conversion, livelihood, moulting, but not significantly influence (P> 0.05) on SR mangrove crabs. The results shows that the best treatment for absolute weight growth was found in 7% feeding of biomass weight (P3), which was 80.00 g, specific growth rate of 1.53%, average moulting time of 18.66 days with survival rate 83 , 33%, and the best feed conversion is 4.10.Keywords :Mud crab; Food; Growth; Moulting; Life-long rate